Investasi Cerdas di Tengah Pandemi: Webinar Otoritas Jasa Keuangan (OJK) - Dewa Ayu Oki Astarini; Anthony Angrawan; R. Ayu Ida Aryani; Ikang Murapi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
This devotional activity aims to provide education about smart investments that can be done in the midst of the covid 19 pandemic, namely through investments in the Indonesian Capital Market and analysis that investors need to do before starting to invest. This devotion is also one way to motivate students as millennials to have a paradigm of investment society.This devotion was conducted in the form of a webinar event "smart investment in the middle of the pandemic" with participants of Bumigora University students. The webinar aims to add insight into how to invest in stocks, indicators to consider and strategies for stock investments that generate income with controllable risks. In addition, in this devotion is given a simulation of how to utilize the existing technology on smartphones for ease in investing through investment applications in playstore..